TOBACCO UNION PRESIDENT OPPOSES 75 CENT CIGARETTE TAX INCREASE (Tufts Archival Research Center, 2007)
Newsletter from Frank Hurt of the Bakery, Confectionary and Tobacco (BC&T) Workers International Union. Argues against a 75 cent increase in the cigarette tax in order to fund health care. Contends that it is too unstable a revenue source and unfairly affects southern workers as well as lower income families.